2019
DOI: 10.5116/ijme.5c39.b55b
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the role of near-peer teaching in critical appraisal skills learning: a randomized crossover trial

Abstract: Objectives The study sought to evaluate near-peer tutors’ teaching of critical appraisal skills to medical students as an aspect of Evidence-based Medicine. Methods In a randomized crossover trial, 241 students completing a Clinical Epidemiology and Evidence-based Medicine (CE-EBM) module in the Faculty of Medicine Universitas Indonesia (FMUI) were randomly assigned to intervention or control groups. During tutorial sessions, intervention group participants were assigne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
41
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 27 publications
0
41
1
1
Order By: Relevance
“…42 With the varying amount of questions used in other NPT programme tests, a further validated tool is required to determine the number of questions required in each test to provide a perfect balance between not detracting from valuable session time while also giving a true assessment of students’ knowledge. 40 43 44…”
Section: Discussionmentioning
confidence: 99%
“…42 With the varying amount of questions used in other NPT programme tests, a further validated tool is required to determine the number of questions required in each test to provide a perfect balance between not detracting from valuable session time while also giving a true assessment of students’ knowledge. 40 43 44…”
Section: Discussionmentioning
confidence: 99%
“…Based on faculty observation, the NPMs showed consistent maturity in their advice and growing awareness of their own limitations. Others have also reported that NPMs are as effective and are often better received than more formal tutors [22]. NPMs did not receive formal training for their roles having been previous participants in the program and their quality performance did not warrant it.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that the outcome of near-peer programmes is as effective as consultant-and faculty-led teaching and are potentially more popular among trainees, possibly due to proximity in age and experience (13)(14)(15)(16)(17). Designing and participating in such programmes also provides trainees with teaching opportunities, enhances their knowledge of the subject and develops their communication, presentation and leadership skills.…”
Section: Discussionmentioning
confidence: 99%